Die wirtschaftsgeographischen Verhältnisse Ecuadors: Erster Bericht einer Forschungsreise nach Südamerika 1957/58 - Sick, Wolf-Dieter (ERDKUNDE, 1959)
The purpose of this paper is the presentation of a review of the present economic-geographical conditions of Ecuador, based on field studies made by the author during 1957/58. The varied natural endowment with its close juxtaposition of rain forests and dry regions, and of riot tropical lowland and cool high mountains makes possible a diversified agricultural landuse. Although Ecuador, as an underdeveloped country, has not yet made full use of these potentialities, it is nevertheless a model for economic-geographical studies in the tropics. The development of cultivation and the distribution of the foremost crops, bananas, cocoa, coffee, rice, cotton and sugar cane in the coastal regions, and cereals, maize, potatoes and fruit in the Andean highlands, as well as development and distribution of animal husbandry are briefly pointed out. The problems of crop rotation, manuring, crop improvement, and mechanization are touched upon. Measures for irrigation and against soil erosion deserve particular attention, one of the latter being re-afforestation. Modern farm management is so far not widely found, especially in the Andean regions, but a promising start has been made. In addition to the lack of capital, a major handicap lies in the unfavourable farm sizes, the contrast between giant estates with extensive land use, and numerous uneconomic small holdings, retarding the social progress of the country. Intensification of agriculture and the opening up of new areas of colonization are the most important tasks for developing the economy. For this improved education of the very heterogeneous population is, in addition to financial assistance, a decisive condition. After agriculture the present state of industry, so far little developed, and the insignificant mining is sketched out. The state of communications is of paramount importance in linking the very differently endowed parts of the country; despite some progress a further development of communications between coast, highland and the eastern lowland, as yet still largely not opened up, is an urgent requirement for further economic progress. The accompanying map shows the present distribution of crops. A more detailed treatment of the economic geographical problems together with a regional classification of Ecuador as regards its economic geography is to follow in a forthcoming paper by the author.